Bibliometric analysis of antimalarial drug resistance - Zhang, Jialu; Shahbaz, Muhammad; Ijaz, Muhammad; Zhang, Huimin (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Malaria has always been a serious infectious disease prevalent in the world.Antimalarial drugs such as chloroquine and artemisinin have been the main compounds used to treat malaria. However, the massive use of this type of drugs accelerates the evolution and spread of malaria parasites, leading to the development of resistance. A large number of related data has been published by researchers in recent years. CiteSpace software has gained popularity among researchers of late years, for its ability to help us get the core information we want in a mass of articles. In order to analyze the hot spots and develop trends in this field through the visual analysis, this study used CiteSpace software to summarize the available data in the literature to provide insights.Method: Relevant literature was collected from the Web of Science Core Collection (WOSCC) Method: Relevant literature was collected from the Web of Science Core Collection (WOSCC) from January 1, 2015 to March 29, 2023. CiteSpace software and Microsoft Excel were used to analyze and present the data, respectively. Results: A total of 2561 literatures were retrieved and 2559 literatures were included in the analysis after removal of duplications. An irrefutable witness of the ever-growing interest in the topic of antimalarial drug resistance could be expressed by the exponentially increased number of publications and related citations from 2015 to 2022, and its sustained growth trend by 2023. During the past seven years, United States, the Oxford University, and David A Fidock are the country, institution, and author with the most publications in this field of research, respectively. We focused on the references and keywords from literature and found that the research and development of new drugs is the newest hot spot in this field. More and more scientists are devoted to find the new antimalarial drugs.